Implementation of Digitalization of Goods and Services Tax Services For Certain Food and / or Beverages and Its Contribution to Regional Taxes in Kutai Kartanegara Regency - Wahyuni; Jumaidi; Sudirman (Global Research Collaboration, 2026)
This research aimed to examine the implementation of service digitalization and its effect on PBJT Food and/or Beverage revenue. The study employed a mixed methods approach, consisting of qualitative analysis using Edward III’s policy implementation model and an assessment of the growth and contribution of PBJT Food and/or Beverage to regional tax revenue, as well as quantitative analysis using multiple linear regression. The qualitative analysis examined four main variables in policy implementation, namely communication, resources, disposition, and bureaucratic structure, in order to understand the effectiveness of the implementation of restaurant tax service digitalization. Meanwhile, the quantitative analysis aimed to examine the effect of the number of e-SPTPD (electronic Regional Tax Return) and TP2DD (Regional Digitalization Acceleration and Expansion Team) as independent variables on PBJT Food and/or Beverage revenue as the dependent variable. The results of the study indicated that, qualitatively, the implementation of the digitalization of PBJT Food and/or Beverage services in Kutai Kartanegara Regency had been carried out quite effectively. The factors of communication, resources, disposition, and bureaucratic structure mutually supported the implementation of digitalized regional tax services. However, several obstacles still remained, particularly in terms of communication consistency, internet network stability, and the community’s digital literacy. The average growth of PBJT Food and/or Beverage revenue reached 11.27% per year, with an average contribution of 32.98% to the Regional Tax revenue of Kutai Kartanegara Regency. Quantitatively, the regression results showed that the number of e-SPTPD and TP2DD had a positive and significant effect on the revenue from PBJT on Food and/or Beverages, both partially and simultaneously. Every increase of 1 unit in e-SPTPD increased the average PBJT revenue from Food and/or Beverages by IDR 729,435, while TP2DD was able to increase the average PBJT revenue from Food and/or Beverages by a considerably high amount, namely IDR 765,300,000 per month. This indicated that the increased use of electronic tax reporting systems as well as the optimization of TP2DD’s role could improve PBJT revenue from Food and/or Beverages.